EUFEMISME DAN DISFEMISME PADA JUDUL BERITA KASUS PELECEHAN SEKSUAL DI KOMPAS.COM JANUARI (2024–2025) - Fauziana Ulfi; Dodi Firmansyah; Ade Anggraini Kartika Devi (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study discusses the role of semantics in news headline writing in mass media, particularly focusing on the use of euphemism and dysphemism. Choosing the right diction is essential to convey meaning accurately and avoid misunderstandings. Euphemisms provide a softened impression and uphold ethical standards, especially in sensitive issues such as sexual violence. In contrast, dysphemisms tend to be harsh and can trigger negative reactions. Headlines that deviate from semantic principles and journalistic ethics may reduce public trust in the media. Therefore, semantic understanding is crucial for producing informative and ethical news. This research employs a qualitative approach with a descriptive method. The researcher uses Allan & Burridge’s theory of euphemism forms, and the functions of euphemism as proposed by Sutarman, Wijana & Rohmadi, and Allan & Burridge. The researcher also applies Allan & Burridge’s theory of dysphemism forms and the functions of dysphemism by Sutarman and Allan & Burridge. The analysis found 19 instances of euphemism and 7 of dysphemism, each with varying forms and functions. Euphemisms were predominantly used for softening language, while dysphemisms served to intensify fear and clarify meaning. These findings have positive implications for Indonesian language learning, especially as source material and instructional content for news text in the Merdeka Curriculum. This study is also recommended for students, teachers, and researchers as a reference for understanding and developing linguistic studies in mass media.